(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2021)
Background: Women being the back bone of any sound society where she has to undergo the pressure of maintaining sound health which needs a constant check on kind of food consumed by women. This results in adoption of various diet food plans but this adoption highly depends on the acceptance of diet food on various palatability factors. Objectives: To study the factors that affects the acceptability of diet food. To find the most dominating palatability factor influencing the consumption of the diet food. Methodology: A descriptive cross – sectional design was adopted. Women in an age group of 25 to 55 years were selected through purposive sampling. A structured survey instrument was used for data collection form 174 women from Gurdaspur and adjoining cities such as Pathankot and Amritsar. Results: The most dominating palatability factors weretexture (56.1), taste (47.5) in average scores and then followed by aroma(40.6) and appearance (38.1) in average score. The most important acceptability factor was the satisfaction level (0.785) Relative index of importance for the food which is considered good for health and weight loss. Conclusion: Respondents hasgiven their responses towards more basic palatability dominant factors which decide the consumption patterns along with the acceptability of food on the lines of satisfaction level due the improvement of health.